Primary care physician's approach for mental health impact of COVID-19 - Rohilla, Jitendra (J Family Med Prim Care, 2020)
As the world struggles to control coronavirus infection with the exhausting capacity of health care systems globally, the role of primary care physician and family physician becomes more important as the first point of contact with the community. Limited availability of mental health services in India requires general practitioners to deal with psychological disorders arising due to infection outbreak and its restrictive control strategies. This article discusses what and how primary physicians can manage the psychological burden of a pandemic, and therefore, reducing the reliance on mental health specialist.